Mechanical Force-Induced Blue-Shifted and Enhanced Emission for AIEgens - Chang-Sheng Guo; Xiao-Long Su; Yu-Ting Yin; Bo-Xuan Zhang; Xin-Yi Liu; Rui-Peng Wang; Pu Chen; Hai-Tao Feng; Ben-Zhong Tang (Biosensors, 2022)
Mechanochromic (MC) luminescence of organic molecules has been emerging as a promising smart material for optical recording and memory devices. At the same time, pressure-induced blue-shifted and enhanced luminescence are rarely reported now. Herein, a series of cyanostilbene-based AIEgens with different substituents were synthesized to evaluate the influence of morphology transformation and push-pull electronic effect on the MC luminescence. Among these luminophores, compound 1 with one cyano group and diethylamino group was more susceptible to mechanical stimuli and obtained blue-shifted and enhanced fluorescence in response to anisotropic grinding. Powder X-ray diffraction patterns indicated that the MC behaviors were ascribed to the solid-state morphology transition from crystal-to-crystal. Analysis of crystal structures revealed that loose molecular packing is a key factor for high high-contrast MC luminescence. The smart molecular design, together with the excellent performance, verified that luminophores with twisted structures are ideal candidates for MC luminogens.